Utrata wartości aktywów w jednostkach gospodarczych - Siudek, Tomasz (Devaluation of Assets in Business Entities, 2005)
The paper presents the problem of the loss in value of assets in economic entities. The methodology of estimation of adjustments resulting from reduction in assets value has been provided. Additionally, the methods to measure the economic value of assets have been illustrated. Some shortcomings and advantages of the assessment of the economic value by using two approaches, namely the market based valuation and the income based valuation, have been listed. Finally, some consequences of those assessments both for property value and earnings in business units have been shown.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 249-257